Some new coincidence point results for single-valued and multi-valued mappings in $b$-metric spaces via digraphs - S. K. Mohanta; R. Kar (Математичні Студії, 2020)
We introduce the concept of generalized $F$-$G$-contraction and prove some new coincidence point results for single-valued and multi-valued mappings in $b$-metric spaces endowed with a digraph $G$. Our results generalize and extend several well-known comparable results including Nadler's fixed point theorem for multi-valued mappings. Moreover, we give some examples to justify the validity of our main result.